Advances and future perspectives in biotechnological and bioconversional of dates byproducts - Musa, Khalid Hamid; Elnour, Ahmed Adam Hassan Mohammed (Elsevier B.V., 2024)
Date production poses significant environmental and economic problems. Conventional waste management methods are insufficient to address these issues. However, microorganisms can convert date waste into valuable products, thus making bioconversion a sustainable solution. Objective: This study investigated how bioconversion processes can manage date byproducts, focusing on producing beneficial compounds and nutrients in different industries. In addition, it emphasizes the importance of protecting the environment and managing waste responsibly in the data industry. Methods: This study studies recent research on bioconversion processes using fungi and bacteria to convert date waste into bioactive compounds, enzymes, and polysaccharides. It determines whether these products can be used in different sectors, such as food, pharmaceuticals, and cosmetics. It examines methods for producing energy and recycling materials such as biogas, electricity, and biofuels. Results: Bioconversion processes can transform date waste into valuable resources, thereby benefiting the economy and the environment. Research has demonstrated the successful production of antioxidants, enzymes, and polysaccharides from date waste, with applications in multiple industries. Conclusion: Repurposing food waste as a useable resource reduces waste and opens up new economic opportunities. By leveraging the capabilities of microorganisms, waste can be converted into valuable products, thereby contributing to environmental preservation and economic advancement. Improving biotechnology to hone bioconversion processes and to make them cheaper is essential. Recommendation: To maximize the potential for bioconversion, concerted research and development endeavors are essential. Priority should be given to refining bioconversion processes, innovating new products, and addressing the challenges associated with implementation and regulation, especially in developing nations. Researchers, industries, and policymakers must collaborate to manage date waste and promote sustainable development through bioconversion.